Integrated dynamometric, kinematic and electromyographic characterisation of a swimming track start block phase - A pilot study - Vitor, M.; de Jesus, K.; Mourão, K.; Tribuzi, S.; Gonçalves, P.; Marques, M.; Roesler, H.; Vaz, M.; Vilas-Boas, J.P.; Fernandes, R.J. (Central European Journal of Sport Sciences and Medicine, 2016)
This study presents a complete biomechanical analysis of the block phase of a swimming modified track start. Kinetic, kinematic and electromyography (EMG) data were collected. The forces produced by the swimmer on the block, the EMG of eight muscles and the kinematics of the centre of mass (CM) were recorded. A national-level swimmer performed three repetitions of a track start in a dynamometric starting block. Temporal instants `reaction time`, `hands take-off`, `rear foot take-off` and `front foot take-off` were identified. Results show the peak forces (Fmax) produced by the most dynamic limb in each sub-phase delimited by mentioned instants (right hand take-off: Fmax vertical = 103 N; rear foot take-off: Fmax antero-posterior = 524 N; front foot take-off: Fmax vertical = 634 N). The CM revealed a descendent vertical trajectory along the block phase. Mean resultant speed at front foot take-off was 4.092m/s. The muscles with highest values of integral EMG (iEMG) were the tibialis anterior during hands take-off, Biceps Femoris and Gluteus Maximus during rear foot take-off, respectively 41.17%, 52.96% and 36.37% of the maximum isometric voluntary contraction (%MIVC). The study demonstrates an effective characterisation of the block phase in swimming starts with potential to evaluate the swimmers performance in the track start, using different back plate positioning.